APPLICATION OF THE CONCEPT OF KALA IN RELIGIOUS LIFE IN BANGLI SOCIETY - Dharma, I Wayan Yudhasatya (Vidyottama Sanatana: International Journal of Hindu Science and Religious Studies, 2024)
Time is the most valuable thing to have and at the same time it is also the easiest thing to waste. So on this occasion the author determined this research with the title "Application of the Kala Concept in the Religious Life of the Hindu Community in Bangli Regency". Oriented to this background, a discussion can be formulated relating to the application of the Kala concept in the socio-religious life of the Hindu community in Bangli Regency. To explain the problem above, the author uses qualitative research. In this case, the author was directly involved in collecting data by means of observation, documentation and interviews with informants in Bangli Regency. Apart from that, this research uses types of library data such as books, journals, or previously existing scientific works that have a correlation with the research being carried out. From the research conducted, it can be described as follows; (1) The Kala concept is applied in the ruatan procession, through the Sapuh Leger Wayang performance, the Sudamala procession, and the Mapandes. (2) Application of the concept of Kala in art, where Kala and its mythology are a source of inspiration in artistic trends that have developed over time. (3) The concept of Kala is applied in religious ceremonies, especially through the Bhuta Yadnya ceremony. (4) The concept of Kala is also a source of ethics in the life of the Bangli people, where there are several taboos that the community cannot do because it has the consequence of receiving punishment from Kala. (5) The concept of Kala by the Bangli people is also applied as a magical means of protection, by creating various symbols of Kala (rerajahan).